Nemolizumab in prurigo nodularis up to 100 weeks: OLYMPIA LTE interim analysis - Legat, Franz; Kwatra, Shawn G.; Reich, Adam; Boulinguez, Serge; Tsianakas, Athanasios; Sauder, Maxwell; Barbarot, Sebastien; Szepietowski, Jacek C.; Conrad, Curdin; Pink, Andrew E.; Weisshaar, Elke; Misery, Laurent; et al. (Journal of the European Academy of Dermatology and Venereology, 2025)
Background: Prurigo nodularis (PN) is a neuroimmune skin disease characterized by the presence of chronic itch (≥6 weeks) and multiple white-pink papules, nodules and/or plaques. Objectives: The OLYMPIA long-term extension (OLYMPIA-LTE) trial evaluates long-term, over 184 weeks, safety and efficacy of nemolizumab in adults with moderate-to-severe PN. Methods Adults with moderate-to-severe PN, who completed phase 2b (NCT03181503) and phase 3 (OLYMPIA 1&2) lead-in trials, were eligible for the ongoing OLYMPIA-LTE trial. Patients receiving nemolizumab monotherapy (continuous-nemolizumab) during lead-in trials continued their regimen, while those on placebo (nemolizumab-naïve) initiated nemolizumab monotherapy. The primary endpoint was long-term safety. Efficacy assessments included the proportion of patients achieving a ≥4-point improvement from baseline Peak Pruritus Numerical Rating Scale (PP-NRS4), Sleep Disturbance Numerical Rating Scale (SD-NRS4) and Dermatology Life Quality Index (DLQI4) scores, Investigator's Global Assessment (IGA) score 0/1 (clear/almost clear), and 75% healed pruriginous lesions (Prurigo Activity and Severity score item-5b). Observed cases up to week 100, regardless of rescue medication, are presented, without imputation of missing data. Results: At interim analysis data cut-off (21 July 2024), 290/508 (57%) patients completed week 100 (median exposure: 839.5 days). Treatment-emergent adverse events (TEAEs) occurred in 89% of patients (452/508; exposure time-adjusted incidence rate: 197.5/100 patient-years) and were mostly mild/moderate (26%/52%) in severity. TEAEs occurring in ≥5% of patients at any given year were COVID-19 (28%), nasopharyngitis (20%), upper respiratory tract infection (13%), neurodermatitis (worsening of PN; 13%), back pain (9%), headache (9%), arthralgia (9%), cough (8%), hypertension (8%) and nummular eczema (8%). At week 100, among evaluable patients treated with nemolizumab, 92% achieved PP-NRS4, 86% SD-NRS4, 91% DLQI4, 74% IGA 0/1 and 84% observed healing of >75% of pruriginous lesions. Conclusions: Long-term treatment with nemolizumab was well tolerated and led to disease control with clinically meaningful improvements in itch intensity, pruriginous lesions and quality of life. Clinical Trial Registration No NCT04204616, RD.06.SPR.202699 and 2019-004294-13 (EudraCT Number).
Vorab veröffentlicht: 17. Dezember 2025
Gesehen am 20.02.2026